Analysis of the QuantiFERON-CMV assay, CMV viraemia and antiviral treatment following solid organ transplantation in Western Australia - Thompson, G.; Boan, P.; Baumwol, J.; Chakera, Aron; MacQuillan, G.; Swaminathan, S.; Lavender, M.; Flexman, J.; James, I.; John, M. (Lippincott Williams & Wilkins, Ltd., 2018)
Prevention of cytomegalovirus (CMV) infection remains an important aspect of improving long term outcomes of solid organ transplantation and currently relies on prophylactic antiviral medication and early detection of viraemia or disease. Uptake of diagnostic tools to personalise assessment of CMV immunity and guide interpretation of viral testing remains low. We assessed the QuantiFERON-CMV assay in 54 Western Australian recipients of renal, heart, lung or liver allografts to determine the relationship between CMV-specific immunity, viraemia and disease following cessation of antiviral prophylaxis. We carried out an initial validation study which demonstrated that the QuantiFERON-CMV assay is highly precise and strongly correlated with CMV-specific antibodies in 30 healthy blood donors (sensitivity 82%, specificity 95%). In the solid organ transplant recipients we examined, the prevalence of asymptomatic CMV viraemia was high at 61% but only two patients ultimately developed CMV disease, both of whom had negative QuantiFERON-CMV responses, indicating lack of CMV T-cell immunity. The vast majority (94%) of patients who had spontaneous resolution or stability of asymptomatic CMV viraemia without any antiviral treatment had positive QuantiFERON-CMV responses. Positive QuantiFERON-CMV responses at cessation of antiviral prophylaxis were significantly associated with pre-transplant CMV seropositivity and the development of asymptomatic viraemia post-transplantation. Overall, 27% of patients were recommenced on antiviral therapy because of asymptomatic CMV viraemia. Patients with non-reactive QuantiFERON-CMV responses had earlier onset, higher level CMV viraemia compared to those with positive QuantiFERON-CMV responses, although the difference did not reach statistical significance. QuantiFERON-CMV results may contribute to decision making in concert with the serological risk profile, net state of immunosuppression and CMV viral load.